Dangdut vs K-Pop in BIPA Learning in South Korea - Wati Istanti; Nike Widya Kusumastuti; Agus Sulaeman; Akhmad Fauzan (Universitas Muhammadiyah Malang, 2025)
Dangdut is one of Indonesia’s popular traditional music genres, rooted in Arabic, Malay, and Hindustani musical influences since the 1940s. Indonesia and South Korea share similarities in utilizing music for cultural promotion. Indonesia introduces its culture through dangdut music, while South Korea promotes its cultural identity through K-pop. K-pop is widely recognized among Indonesian youth, whereas dangdut remains relatively unknown in South Korea. Meanwhile, teaching Indonesian as a second language has developed significantly in South Korea, notably at Hankuk University of Foreign Studies (HUFS). Introducing dangdut music in BIPA (Bahasa Indonesia for Foreign Speakers) instruction offers a strategic potential that can be compared to K-pop as an instructional medium. This study aims to (1) explore the characteristics of dangdut and K-Pop suitable as learning materials for BIPA in South Korea; and (2) describe the implementation of cultural diplomacy through dangdut music in the BIPA program. This research employed a qualitative descriptive method with a case study design. Primary data were obtained through observations, questionnaires, and interviews involving students, instructors, and program coordinators of BIPA at HUFS. Secondary data were collected from program documents and relevant literature. Data were analyzed using Miles and Huberman’s interactive analysis model. The findings indicate that: (1) the communicative and contextual nature of dangdut is suitable for BIPA instructional materials, and K-Pop’s popularity is leveraged to attract learner interest; and (2) the use of dangdut music in BIPA instruction serves as a form of cultural diplomacy that strengthens intercultural relations. This study contributes to facilitating South Korean learners in acquiring the Indonesian language and ultimately enhancing the achievement of cultural diplomacy between the two countries.